The aims of religious education in Lesotho - Ramahadi, Evangeline Dineo (My University, 2015)
This dissertation attempts to identify the aims of Religious Education in Lesotho secondary schools. The time of missionary .enterprise in the Nineteenth Century has been followed in the second half of the Twentieth Century by dynamic political and socioeconomic change. This period is marked by considerable uncertainty about the aims of religious education.